Peningkatan Keterampilan Psikomotor dan Hasil Belajar Siswa melalui Model Direct Instruction berbantuan Praktikum pada Materi Pengukuran - Marcelina, Susi; Cahaya, Sri; Triana, Yulia; Normala; Yulinae; Hartanto, Theo Jhoni (PendIPA Journal of Science Education, 2024)
The low psychomotor skills and students' learning outcomes in class VII of SMPN 1 Katingan Hilir motivate this research. The purpose of this study is to improve the psychomotor skills and learning outcomes of students through the application of the direct instruction model with the practicum method. This research is classroom action research where each cycle consists of planning, implementation, observation, and reflection stages. The subjects of the study were all 25 students of class VII of SMPN 1 Katingan Hilir. Data on students' psychomotor skills were obtained through performance tests, while data on students' learning outcomes were collected through written tests. The results showed an increase in students' psychomotor skills and learning outcomes from cycle I to cycle II. In cycle I, 44% of students achieved the expected learning outcomes, and 68% of students had good psychomotor skills. In cycle II, 92% achieved the expected learning outcomes, and 88% of students had good psychomotor skills. This increase shows that the direct instruction model with the practicum method can improve students' psychomotor skills and learning outcomes in measurement material.